Heat transfer study of 3-D printed air-cooled heat sinks - See, Yao Song (2016)
This report examines the heat transfer of four different heat sink designs that were fabricated using Selective Laser Melting (SLM). All heat sinks were subjected to an impingement air flow. The four heat sink designs consist of a cylindrical heat sink, and three other axially perforated designs namely the hollow, tapered and nozzle heat sinks. The fabrication of these heat sinks had determined that SLM was capable of producing intricate designs with maximum error of approximately 0.3 mm. Theoretical studies conducted on the heat sink designs showed that a single hollow pin fin performed better than a single cylindrical pin fin of similar mass due to the axial perforation that provided additional surface areas for heat transfer. The experimental results showed that the Nusselt numbers of the cylindrical heat sink are up to 9.9% higher as compared to other heat sinks with the nozzle height of 6 mm, and up to 16.6% higher at 18 mm nozzle height. However, the heat transfer for each unit cell for the cylindrical heat sink performed worse than the other heat sinks, with the tapered heat sink being the best, performing a maximum of 84.6% and 87.2% better than the cylindrical heat sink, followed by the nozzle, hollow and cylindrical heat sink. This is due to the additional internal surface areas caused by adding perforations, for heat transfer. The present investigation shows that the intricate axially perforated heat sink designs resulted in higher heat transfer performances than some conventional heat sinks.